Nursing care of a patient after limb amputation - case study - Jędrzejkiewicz, Bernadeta (Journal of Education, Health and Sport, 2019)
Amputation is the operative, partial or complete cutting off of an organ; the term mainly used for limbs. Traumatic amputation of the limb is one of the oldest surgical procedures. Currently, thanks to the progress of medicine, it is performed less and less often, mainly in cases of malignant tumors, advanced ischemia or complete interruption of blood circulation in the limbs, and also with significant traumatic injuries. The missing part of the limb can be filled with a prosthesis. The most preferred is amputation of the myoplastic limb, i.e. cutting off the limb in a suitable place, or part thereof, followed by suturing of antagonistic muscle groups together and peripheral cutting of the stump bone. Thanks to myoplastic amputation, a functional, well-supplied and painless stump is obtained, suitable for prosthesis.